Characteristics of Left Atrial Deformation Parameters and Their Prognostic Impact in Patients with Pathological Left Ventricular Hypertrophy: Analysis by Speckle Tracking Echocardiography. (8th May 2015) - Iio, Chiharuko; Inoue, Katsuji; Nishimura, Kazuhisa; Fujii, Akira; Nagai, Takayuki; Suzuki, Jun; Okura, Takafumi; Higaki, Jitsuo; Ogimoto, Akiyoshi
Abstract : Background: The pathological process of left ventricular (LV) hypertrophy is associated with left atrial (LA) remodeling. This study was aimed to evaluate the prognostic value of LA strain parameters in patients with pathological LV hypertrophy. Methods: This study included 95 patients with hypertensive heart disease (HHD: n = 24), hypertrophic cardiomyopathy (HCM: n = 56), cardiac amyloidosis (CA: n = 15), and control subjects (n = 20). We used two‐dimensional speckle tracking echocardiography (STE) to analyze LA global strain. LA electromechanical conduction time (EMT) at the septal (EMT‐septal) and lateral wall (EMT‐lateral), and their time difference (EMT‐diff) were calculated. The incidence of cardiac death and heart failure hospitalization was defined as major cardiac events and that of atrial fibrillation as secondary outcome. Results: Left atrial volume index was increased and LA booster strain was decreased in the HCM and CA groups compared with the HHD group. EMT‐lateral was increased in the diseased groups compared with the control. EMT‐diff was prolonged in the CA group compared with the HCM group. During the follow‐up period (mean 3.4 years), major cardiac events and atrial fibrillation occurred in 17 and 13 patients, respectively. The occurrence of atrial fibrillation was associated with CA etiology, E/e′, LA volume index, LAa, and EMT‐lateral. The incidence of major cardiac events was independently correlated with LA volume index and EMT‐diff in multivariate analysis. Conclusion: This study suggested that the EMT‐diff could discriminate patients with a high risk of cardiac events among patients with pathological LV hypertrophy.